The Trouble with Lawyers - Rhode, Deborah L (Oxford University Press, 2015)
By any measure, the law as a profession is in serious trouble. Americans' trust in lawyers is at a low, and many members of the profession wish they had chosen a different path. Law schools, with their endlessly rising tuitions, are churning out too many graduates for the jobs available. Yet despite the glut of lawyers, the United States ranks 67th (tied with Uganda) of 97 countries in access to justice and affordability of legal services. The upper echelons of the legal establishment remain heavily white and male. Most problematic of all, the professional organizations that could help remedy these concerns instead jealously protect their prerogatives, stifling necessary innovation and failing to hold practitioners accountable. Deborah Rhode's The Trouble with Lawyers is a comprehensive account of the challenges facing the American bar. She examines how the problems have affected (and originated within) law schools, firms, and governance institutions like bar associations; the impact on the justice system and access to lawyers for the poor; and the profession's underlying difficulties with diversity. She uncovers the structural problems, from the tyranny of law school rankings and billable hours to the lack of accountability and innovation built into legal governance-all of which do a disservice to lawyers, their clients, and the public. The Trouble with Lawyers is a clear call to fix a profession that has gone badly off the rails, and a source of innovative responses.